2020
DOI: 10.1124/jpet.120.265496
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Value of Urotensin II Receptor Antagonist in Chronic Kidney Disease and Associated Comorbidities

Abstract: Chronic kidney disease (CKD) remains a common disorder leading to growing health and economic burden without curative treatment. In diabetic patients, CKD may result from a combination of metabolic and non-metabolic-related factors with mortality mainly driven by cardiovascular events. The marked overactivity of the urotensinergic system in diabetic patients implicates this vasoactive peptide as a possible contributor to the pathogenesis of renal as well as heart failure. Previous preclinical studies with urot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The response to a drug can be altered by pathologic conditions (acute and chronic illness and kidney disease) by Decreased receptor number (Emax) and sensitivity (EC50), Decreased receptor binding and altered signal transduction. It was found that vancomycin with a time-dependent antibacterial effect showed increased efficacy and decreased toxicity when administered by prolonged infusion rather than short-term infusion [6]. Similar effect is noted with Meropenem and Piperacillin, where the dosage was based on pharmacodynamics regimens.…”
Section: Introductionmentioning
confidence: 74%
“…The response to a drug can be altered by pathologic conditions (acute and chronic illness and kidney disease) by Decreased receptor number (Emax) and sensitivity (EC50), Decreased receptor binding and altered signal transduction. It was found that vancomycin with a time-dependent antibacterial effect showed increased efficacy and decreased toxicity when administered by prolonged infusion rather than short-term infusion [6]. Similar effect is noted with Meropenem and Piperacillin, where the dosage was based on pharmacodynamics regimens.…”
Section: Introductionmentioning
confidence: 74%
“…The UT receptor and endogenous ligands are widely expressed in various tissues from fish to mammals [2,3]. Clinical studies have shown that U-II/UT expression levels are closely associated with a variety of diseases, such as cardiovascular [4], liver [5], and kidney diseases [6]. It has been suggested that U-II may play a key role in glucose and fat metabolism [7][8][9].…”
Section: Introductionmentioning
confidence: 99%